Proline-promoted dehydroxylation of α-ketols. Issue 40 (28th August 2019) - Mostinski, Yelena; Lankri, David; Konovalov, Yana; Nataf, Riva; Tsvelikhovsky, Dmitry
Abstract : A new single-step proline-potassium acetate promoted reductive dehydroxylation of α-ketols is reported. We introduce the unexplored reactivity of proline and, for the first time, reveal its ability to function as a reducing agent. Abstract : A new single-step proline-potassium acetate promoted reductive dehydroxylation of α-ketols is reported. We introduce the unexplored reactivity of proline and, for the first time, reveal its ability to function as a reducing agent. The developed metal-free and open-flask operation generally results in good yields. Our protocol allows the challenging selective dehydroxylation of hydroxyketones without affecting other functional groups.